2023
DOI: 10.1038/s41467-023-38951-2
|View full text |Cite|
|
Sign up to set email alerts
|

Deficit of homozygosity among 1.52 million individuals and genetic causes of recessive lethality

Asmundur Oddsson,
Patrick Sulem,
Gardar Sveinbjornsson
et al.

Abstract: Genotypes causing pregnancy loss and perinatal mortality are depleted among living individuals and are therefore difficult to find. To explore genetic causes of recessive lethality, we searched for sequence variants with deficit of homozygosity among 1.52 million individuals from six European populations. In this study, we identified 25 genes harboring protein-altering sequence variants with a strong deficit of homozygosity (10% or less of predicted homozygotes). Sequence variants in 12 of the genes cause Mend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…This assumption was confirmed by the fact that carrier couples for that particular variant had a high incidence of early miscarriage. In another similar study, Oddsson et al 31 found that disease-causing LoF variants in the DHCR7, GBE1, GLE1, PMM2, PNKP , and TSFM genes have homozygous deficits and have only been reported in compound heterozygous cases, along with a hypomorphic allele that causes partial loss of function. They proposed that variants with a minimum activity level are necessary for successful embryonic development.…”
Section: Discussionmentioning
confidence: 91%
“…This assumption was confirmed by the fact that carrier couples for that particular variant had a high incidence of early miscarriage. In another similar study, Oddsson et al 31 found that disease-causing LoF variants in the DHCR7, GBE1, GLE1, PMM2, PNKP , and TSFM genes have homozygous deficits and have only been reported in compound heterozygous cases, along with a hypomorphic allele that causes partial loss of function. They proposed that variants with a minimum activity level are necessary for successful embryonic development.…”
Section: Discussionmentioning
confidence: 91%
“…Again, recommended thresholds can be used to identify highly constrained genes. The presence of homozygous LoF variants 15 or the deficit of homozygosity among protein-altering variants in the general population 16 are other examples on how information from large sequencing studies can be used to understand gene constraint and potential phenotypic impact. Resources compiling clinical reports on single-gene disorders that enable users to conduct queries based on phenotypic criteria, including the Online Mendelian Inheritance in Man 17 (OMIM), the Human Phenotype Ontology 18 (HPO) and the Monarch Initiative 19 repositories. In this case, the essential nature of a gene is defined by records of early death. Human orthologues of essential genes in different unicellular and multicellular organisms, especially genes that are essential for mammalian organism development 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Again, recommended thresholds can be used to identify highly constrained genes. The presence of homozygous LoF variants 15 or the deficit of homozygosity among protein-altering variants in the general population 16 are other examples on how information from large sequencing studies can be used to understand gene constraint and potential phenotypic impact.…”
Section: Introductionmentioning
confidence: 99%

Lethal phenotypes in Mendelian disorders

Cacheiro,
Lawson,
Van den Veyver
et al. 2024
Preprint